2020
DOI: 10.1016/j.joen.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam Computed Tomographic–based Assessment of Filled C-shaped Canals: Artifact Expression of Cone-beam Computed Tomography as Opposed to Micro–computed Tomography and Nano–computed Tomography

Abstract: Introduction: The present study investigated the assessment of root canal fillings in a series of cone-beam computed tomographic (CBCT) images obtained from endodontically treated mandibular molars with C-shaped canals. Methods: Clinically comparable high (HR) and normal (NR) resolution protocols were selected in 3D Accuitomo 170 (J Morita Corporation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Comparisons between micro-CT and CBCT images of filled root canals show a higher volumetric distortion and artefacts with CBCTs [65,66]. Using nano-CT as a reference, comparison of different CBCT machines and micro-CT demonstrated a significant distortion with all CBCT machines in filled root canals [57]. Micro-CT is considered as the gold standard in studies evaluating quality of root canal filling, root canal morphology, evaluation of canal preparation, and irrigation [65].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between micro-CT and CBCT images of filled root canals show a higher volumetric distortion and artefacts with CBCTs [65,66]. Using nano-CT as a reference, comparison of different CBCT machines and micro-CT demonstrated a significant distortion with all CBCT machines in filled root canals [57]. Micro-CT is considered as the gold standard in studies evaluating quality of root canal filling, root canal morphology, evaluation of canal preparation, and irrigation [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is done by using appropriate settings for scanning and a metal artifact reduction algorithm [55,56]. The expression of artefacts is variable among different CBCT machines [57]. MRI also suffers from similar problems in addition to high cost and long scan times [58,59].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) scanners are often used in laboratory research and have similar general characteristics to CBCT devices (e.g., beam shape and a flat panel detector), but micro-CT involves a smaller FOV, a higher radiation dose, a longer scanning time, and a critical hardware setup. 6 7 8 Although micro-CT scanners are not clinically applicable, several aspects regarding the use of CBCT have been developed and improved based on knowledge gained from micro-CT. For endodontics, the use of high-resolution 3D data has facilitated a better understanding of anatomical challenges, such as flattening, curvature, lateral and accessory canals, apical deltas, and isthmuses, as well as the cleaning, shaping and filling procedures of the root canal system (RCS), 5 8 9 offering better insights into anatomy, pathology, and anticipated endodontic strategies. 5 8 9 10 11 Among the anatomical variations of the root canal, studies have shown that in spite of development of new systems and protocols for cleaning and shaping, isthmuses in root canals continue to be areas that are inaccessible to instruments, resulting in debris accumulation and the maintenance of necrotic pulp tissue and microorganisms inside the RCS, affecting 3D filling and, consequently, clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a deeper understanding of the potential, optimized use, and limitations of CBCT, allowing this modality to be used in a manner that facilitates diagnosis and endodontic planning. 6 12 13 14 15 …”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, the added dimension of CBCT may not improve the diagnosis of inflammation, 6 and the diagnostic value of CBCT can be severely affected by metal artefacts (e.g., from root canal fillings or adjacent implants). 7 Thus, IOR is expected to remain a frequently used imaging modality for routine periapical evaluation before, during, and after treatment. 5 Because of the limited diagnostic efficacy of IOR for periapical lesions, several previous studies have evaluated techniques to optimize lesion detection, including through image postprocessing.…”
mentioning
confidence: 99%